2006
DOI: 10.1007/s10488-006-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Family Resource Scale in Children’s Mental Health: Reliability and Validity among Economically Diverse Samples

Abstract: The adequacy of a family's resources has implications for child and family service processes and outcomes. The field needs tools to assess resources in a manner relevant to children's services research. The purpose of this study was to examine the reliability and validity of the FRS among families caring for children who are receiving mental health services and to compare its measurement quality across samples that differ on economic variables. Exploratory and confirmatory factor analyses supported similar fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…For the former, the scale items and overall score varied as expected by income source those with formal income sources (i.e., employment or public assistance) had more material resources than those who had informal income sources (i.e., informal economy or illegal income). Similarly and consistent with recent analyses of the full FRS (Brannan et al, 2006), those with higher legal incomes had more material resources than those with lower legal incomes. For construct validity, the scale also performed as expected – current drug users had fewer resources than former drugs users and non-drug users.…”
Section: Discussionsupporting
confidence: 86%
“…For the former, the scale items and overall score varied as expected by income source those with formal income sources (i.e., employment or public assistance) had more material resources than those who had informal income sources (i.e., informal economy or illegal income). Similarly and consistent with recent analyses of the full FRS (Brannan et al, 2006), those with higher legal incomes had more material resources than those with lower legal incomes. For construct validity, the scale also performed as expected – current drug users had fewer resources than former drugs users and non-drug users.…”
Section: Discussionsupporting
confidence: 86%
“…Lower scores on the FRS indicate lower perceived adequacy of resources in the childhood home. In previous research, scores on the FRS demonstrated adequate internal consistency, split-half reliability, and criterion-related validity (Brannon et al, 2006; Dunst & Lee, 1987). The Cronbach’s alpha for scores produced by the family resources scale was .95 in this sample.…”
Section: Methodsmentioning
confidence: 82%
“…Original internal reliability (Cronbach's alpha) of the instrument was .92; split-half reliability (Spearman-Brown) was .95; test-retest reliability (2-3 month interval) was .52. The FRS has good construct validity in samples of economically diverse families (Brannan, Manteuffel, Holden, & Heflinger, 2006).…”
Section: Methodsmentioning
confidence: 99%